2014
DOI: 10.1038/srep07480
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Breast Cancer: A Nonlinear Dose-Response Meta-Analysis of Prospective Studies

Abstract: The role of Body Mass Index (BMI) for Breast Cancer (BC) remains to be great interest for a long time. However, the precise effect of nonlinear dose-response for BMI and BC risk is still unclear. We conducted a dose-response meta-analysis to quantitatively assess the effect of BMI on BC risk. Twelve prospective studies with 4,699 cases identified among 426,199 participants and 25 studies of 22,809 cases identified among 1,155,110 participants in premenopausal and postmenopausal groups, respectively, were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 51 publications
2
57
0
2
Order By: Relevance
“…As mentioned earlier, obesity has been shown to be an important risk factor for certain types of cancer [2][3][4][5][6][7]. However, most researchers put more effort to examine the role of general obesity in the etiologies of these malignancies, while paying less attention to the potential detrimental effect of abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, obesity has been shown to be an important risk factor for certain types of cancer [2][3][4][5][6][7]. However, most researchers put more effort to examine the role of general obesity in the etiologies of these malignancies, while paying less attention to the potential detrimental effect of abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that obesity increases the risk of certain types of cancers, including post-menopausal breast cancer, colorectal, endometrial, kidney, and pancreatic cancers [2][3][4][5][6][7]. Obesity may have also contributed to the recent rise in gastric cardia carcinoma and esophageal adenocarcinoma (EAC) incidence over the past decades because the prevalence of obesity has increased dramatically at an accelerating and alarming rate during approximately the same time period [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…El crecimiento de células cancerosas está regulado por varias señales celulares (STAT3, AP-1, MAPK, ERKs) moduladas por la leptina e IL-6, las cuales incrementan la aromatasa, la síntesis de estrógenos y la activación de receptores alfa en las células malignas, llevando a estas células a una mayor proliferación (37) . El incremento del riesgo de cáncer de mama con la obesidad se observa solo en las mujeres posmenopáusicas, encontrándose un RR de 1,12 (IC 95% 1,01 a 1,24) y 1,26 (IC 95% 1,07 a 1,50) cuando el IMC es de 30 y 35 kg/m2, respectivamente (38) . La obesidad también aumenta el riesgo de cáncer de endometrio, riñón, colon y vesícula en mujeres posmenopáusicas.…”
Section: Cáncerunclassified
“…Weight gain is considered to be associated with the risk of breast cancer; however, studies have shown a higher incidence of proliferative lesions in overweight postmenopausal women. A metaanalysis of prospective studies showed that postmenopausal women with a BMI of 25, 30 and 35 kg/m 2 have a relative risk of breast cancer of RR = 1.02 (95% CI: 0.98; 1.06), RR = 1.12 (95% CI: 1.01; 1.24), and RR = 1.26 (95% CI: 1.07; 1.50), respectively, compared with women of normal body weight [62]. There is, however, no similar relationship for premenopausal women.…”
Section: Obesity and Cancermentioning
confidence: 99%